Theatre and memory: some clues for a critical social intervention - Vieites, Manuel Francisco (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
After a literature review on programs of social intervention based on different modalities of theatrical practice, we consider some relevant guidelines in the development of theatre proposals intended to add value to personal and collective stories, but also to people and communities. Similarly, we put forward some theoretical and methodological questions in order to advance a systematic approach to the interplay between theatre and memory, so that they may become a boost for projects linked with educational and social work from a critical perspective.